2014
DOI: 10.1103/physrevlett.113.146601
|View full text |Cite
|
Sign up to set email alerts
|

Impurity-Assisted Tunneling Magnetoresistance under a Weak Magnetic Field

Abstract: Injection of spins into semiconductors is essential for the integration of the spin functionality into conventional electronics. Insulating layers are often inserted between ferromagnetic metals and semiconductors for obtaining an efficient spin injection, and it is therefore crucial to distinguish between signatures of electrical spin injection and impurity-driven effects in the tunnel barrier. Here we demonstrate an impurity-assisted tunneling magnetoresistance effect in nonmagnetic-insulator-nonmagnetic and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
61
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 43 publications
5
61
1
1
Order By: Relevance
“…[31][32][33] It is known that the defects, such as the oxygen vacancies (VO), can be present in the LAO layer during film growth and form localized states (LS) in the LAO band gap. [34][35][36][37] Hence, the IET process via these LS [31][32][33][38][39][40] via LS is the main mechanism of the spin transmission through the LAO layer, the SOT efficiency is expected to exhibit a very strong temperature dependence as indicated by the Glazman-Matveev (GM) theory, 31,33,38,41 , which describes the IET with a power law dependence on temperature.…”
mentioning
confidence: 99%
“…[31][32][33] It is known that the defects, such as the oxygen vacancies (VO), can be present in the LAO layer during film growth and form localized states (LS) in the LAO band gap. [34][35][36][37] Hence, the IET process via these LS [31][32][33][38][39][40] via LS is the main mechanism of the spin transmission through the LAO layer, the SOT efficiency is expected to exhibit a very strong temperature dependence as indicated by the Glazman-Matveev (GM) theory, 31,33,38,41 , which describes the IET with a power law dependence on temperature.…”
mentioning
confidence: 99%
“…This spin accumulation in the NM material generates a small spin-dependent voltage across the junction, which can be removed by Hanle dephasing under an applied magnetic field, producing junction MR with a Lorentzian line shape. Since the observation of such signals at room temperature in Sibased junctions [1], many groups have observed unexpectedly large Lorentzian MR in FM-I-NM heterojunctions, seemingly independent of many known materials parameters and spin-dephasing behavior, generating much debate over the origin of the observed phenomena [5,[7][8][9][10][11][12]. As an example, long spin-coherence times have been inferred in p-type semiconductors despite the known rapid dephasing in the valence band [13].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these studies used a three-terminal method, the reliability of which is now being called into question. Many recent studies demonstrated that signals in the threeterminal geometry originate not from spin accumulation in nonmagnetic channels but from magnetic field-dependent tunneling through localized states [21][22][23][24][25][26][27]. Other studies revealed that NiFe itself generates electromotive forces by the inverse spin-Hall effect (ISHE) [28] and the planar Hall effect [29].…”
mentioning
confidence: 99%